Algebraic equations for constant width curves and Zindler curves. (November 2022) - Rochera, David
Abstract: An explicit method to compute algebraic equations of curves of constant width and Zindler curves generated by a family of middle hedgehogs is given thanks to a property of Chebyshev polynomials. This extends the methodology used by Rabinowitz and Martinez-Maure in particular constant width curves to generate a full family of algebraic equations, both of curves of constant width and Zindler curves, defined by trigonometric polynomials as support functions.